Assembleia de abelhas e efeito da distância de remanescentes florestais na produção de grãos e no valor econômico de Brassica napus (Hyola 420) no sul do Brasil - Oliveira, Rosana Halinski de (2013)
The pollination service is fundamental to the maintenance of biodiversity, human feeding and production of biofuels. This service is threatened by the need of increasing grain production, which enlarge seeding areas causing the degradation of vegetation and biodiversity loss. Thus, in certain crops the narrow dependence of pollinators is related to the quality of adjacent habitats. Studies point out that there is a decline of pollinators with the increase of the distance to forest fragments, promoting a decrease in productivity. Brassica napus, commonly known as canola, fits this scenario. Therefore, the present work aimed to characterize the assemblage of bees in three classes of habitats and analyze the effect of the distances from forest fragments in the grain production and economic value of Brassica napus (Hyola 420) in southern Brazil. The study was conducted in four agricultural areas with canola, in the town of Esmeralda, RS. The diversity of bees was sampled using pan traps in three classes of habitats: (1) canola field in bloom; (2) forest fragment; and (3) ruderal vegetation. In order to evaluate the production of grains by free visitation of insects at 25 m, 175 m and 325 m from the edge of the forest fragments 11 to 18 plants were harvested in the canola fields. For productivity analysis, the plants were harvested in plots of 225 m2 and extrapolated to one hectare. With the projected incomes it was calculated the total economic loss/field using the difference between the most profitable plot (25 m) and the least profitable one (325 m). It was collected 886 bees belonging to 87 species. Among the families collected, Apidae was the most abundant with 441 individuals, being 254 of the Apis melífera species, followed by Halictidae, Andrenidae, Colletidae and Megachilidae. In the three classes of habitats sampled the greatest number of individuals was collected in the ruderal vegetation (50%) followed by the canola field in bloom (47%) and the forest fragment (3%). Eight species were registered in the three classes of habitats, being four of them of native social bees. Besides, it was observed that the species exclusive to determine habitat class were rare, that is, represented by one or few individuals. Eight species were exclusive to the interior of the canola fields, 51 to the ruderal vegetation and six to the forest fragment. Most rare species exibits subsocial or social behavior, small size and inhabit open áreas. It was observed a significant decrease in the mean number of seeds per silique along the edge-interior gradient in all fields, except in the field four. Thus, the forest fragments presented an importante role in the grain yield, and, consequently in the profit, allowing to infer that there is a loss in the grain productivity along the gradiente, which can be altered in at most 2760 kg/ha, which is equivalent to R$ 113,380.80. In the projections done for the four fields, it was stimated that if the field were formed only by plots of 325 m from the forest fragment, the economic loss would be of around R$ 350 thousand. Considering that the sampled fauna in the different agricultural environments is distinct and that most species of bees are potential pollinators agents of canola, it is suggested the maintenance of ruderal and forest areas nearby canola fields. This practice can provide resources to the permanence of pollinators in the area, so that they can perform the pollination service raising the grain productivity and the economic value associated to this.